(untitled) (Journal of Ideas in Health, 2025)
Background: Dry eye disease (DED) is a growing issue, especially in younger groups that use digital devices extensively and among those with vitamin deficiencies. The purpose of this study was to evaluate the relationship between DED among health science students and their digital device use and vitamin D levels. Methods: A cross-sectional study was performed with ninety health science students in Duhok. Participants filled out a standardized questionnaire that asked about their screen time, how they used devices, and their Ocular Surface Disease Index (OSDI) scores. We checked the levels of vitamin D in the blood. Statistical analyses encompassed t-tests, one-way ANOVA, chi-square tests, and Pearson correlation coefficients. Results: Many participants had sustained severe DED (61.1%). The majority of participants (69%) used digital devices for more than 6 hours daily. The average OSDI scores were significantly higher in prolonged users (>6 hours/day: 51.94 ± 20.273) compared to moderate and light users (p = 0.001). Almost 80% of participants had a low level of vitamin D (deficient or insufficient). Vitamin D levels and OSDI scores were strongly negatively correlated (r = -0.622, p < 0.001), while screen time and OSDI scores were positively correlated (r = 0.573, p < 0.001), accounting for 32.8% of the variance. There was a strong link between OSDI intensity and device type (χ² = 19.69, p = 0.02), with people who used more than one device reporting the worst symptoms. There were no strong links between gender (p = 0.146) or educational stress (p = 0.462). Conclusion: Health science students who use digital devices for long periods of time and don’t get enough vitamin D have higher OSDI scores. Interventions should concentrate on regulating screen time, enhancing blink efficiency, and tackling nutritional aspects such as vitamin D supplementation.